2016
DOI: 10.1002/chem.201604508
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticle Loaded Bifunctional Silica Hybrid Material: Preparation and Applications as Catalyst in Hydrogenation Reactions

Abstract: Bifunctional mesoporous silica was prepared by co-condensation of tetraethyl orthosilicate (TEOS) with functionalized organosilanes containing azides or alkoxyamines. Orthogonal functional groups at the particles were selectively addressed in subsequent chemical modifications through "click"-chemistry ("click to ligand" strategy) and radical nitroxide exchange. Palladation with PdCl delivered Pd nanoparticle-loaded silica material bearing sulfoxides and additional aminoamides as stabilizing ligands by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Eckert and Studer reported the synthesis of Pd based bifunctional mesoporous silica nanoparticles bearing stabilizing ligands such as sulfoxides and amino amides (Scheme 22 and 23). [24] The hybrid catalysts were analyzed by IR, TEM/STEM, EDX, and solid-state NMR experiments. The semi-hydrogenation reaction with alkynes and benzyl ethers not only fetched alkenes but also hydrodeoxygenation products.…”
Section: Pd@mesoporous Silica Catalyzed Semi Hydrogenationmentioning
confidence: 99%
“…Eckert and Studer reported the synthesis of Pd based bifunctional mesoporous silica nanoparticles bearing stabilizing ligands such as sulfoxides and amino amides (Scheme 22 and 23). [24] The hybrid catalysts were analyzed by IR, TEM/STEM, EDX, and solid-state NMR experiments. The semi-hydrogenation reaction with alkynes and benzyl ethers not only fetched alkenes but also hydrodeoxygenation products.…”
Section: Pd@mesoporous Silica Catalyzed Semi Hydrogenationmentioning
confidence: 99%
“…Benzylsulfoxide derivatives are the most privileged scaffolds in natural biological products [1], pharmaceutical chemistry [2], and functionalized materials [3]. In particular, benzylsulfoxide derivatives exhibit a wide range of biological properties, such as anti-bacterial activity (Scheme 1I) [4], anti-cancer activity (Scheme 1II) [5], and HIV inhibition (Scheme 1III) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the C-H bond is considered as one of the most useful C-C bond formation strategies [10]. However, many studies have demonstrated that, compared with the C(sp 2 )-H bond functionalization reactions, the application of C(sp 3 )-H bond functionalization reactions remains a challenge in this field [11], as the reactions of C(sp 3 )-H bond functionalization require harsher conditions and activated systems [12]. Given the present challenges, the development of more efficient and environmentally-friendly chemical processes for drug discovery is required [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the magnetic properties provided by magnetite particles often make the separation and recyclability of resulting catalysts much easier. The catalysts based on magnetic particles were efficient in many chemical transformations catalyzed by transition metals, for instance, in the reactions of oxidation [31,32] and epoxidation [33,34], hydrogenation [35,36] and hydroformylation [37,38], and also in olefin metathesis [26,39] and carbon-carbon coupling [40][41][42][43] reactions. Magnetically separable organocatalysts were also prepared based on the particles of magnetite [25,30].…”
Section: Introductionmentioning
confidence: 99%